Soybean Inventory Management in the Production Process of the Semoga Laris Tofu Factory - Putrianti, Elsa Eka; Wahyuda, Wahyuda; Sitania, Farida Djumiati (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
Semoga laris tofu factory is one of the food industry businesses, where the factory processes soybeans into tofu products. The problem that occurs in the management of inventory at the semoga laris tofu factory is that the factory tends to be unprepared for unexpected circumstances, which is caused by the fact that the value of safety stock on raw material inventory has not been determined. At the semoga laris tofu factory hopefully laris there are also capital restrictions on the purchase of raw materials, where the available capital is IDR 30,000,000. This study aims to evaluate the inventory management carried out by the factory by comparing the Min-Max Method, the Economic Order Quantity (EOQ) Method with the tofu factory policy, which after obtaining the optimal Q is then calculated using the working capital constraint method if the results of the optimal Q cannot be met by the available capital. Based on the results of calculations carried out in this study, calculations with the Basic EOQ method have more optimal Q results compared to other methods. However, the basic EOQ calculation exceeds the existing capital limit, because the cost of purchasing raw materials costs IDR 105,450,000. Based on the existence of capital-related restrictions, the calculation is continued with the capital constraint EOQ method. EOQ with this capital constraint has a quantity for one order of 52 bags with a capital cost of IDR 29,640,000.